St. Vincent and the Grenadines : 2014 Article IV Consultation-Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2014 Article IV Consultation highlights that St. Vincent and the Grenadines' economic recovery from the global economic crisis has been curbed by a series of significant natural disasters. These, combined with the economic downturn following the global financial crisis, have prevented the economy from returning to its long-term potential real GDP growth. The overall fiscal balance is estimated to have narrowed to 4.75 percent of GDP in 2014. After an estimated 1.1 percent growth rate in 2014, growth is projected to pick up modestly to 2.1 percent in 2015 on improvements in tourism and agriculture and enhanced implementation of much-needed rehabilitation and reconstruction projects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet